2017
DOI: 10.21275/art20164500
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Changes of Amylose and Amylopectin Content of Paddy during Early Storage

Abstract: Rice (Oryza sativa L.) is the most important cereal crop in Sri Lanka since it is the staple food. Paddy is stored for a considerable period of time before consumption. Amylose and amylopectin contents of rice are very important parameters in determining eating quality of rice. Freshly harvested paddies of three rice varieties BG 300, BG 352 and AT 362 were obtained. Cleaned and dried paddy samples were stored at ambient temperature conditions. Amylose content of each rice variety was determined in every two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…However, by month four of storage, the amylose content did not differ between the RF-treated and untreated rice (Table 3). This result correlated with Patindol et al (2005) and Abeysundara et al (2017), who showed that high storage temperatures lowered amylose content in stored rice. The storage temperatures began to climb in the fourth month of our study, coincident with the arrival of the hot season.…”
Section: Discussionsupporting
confidence: 81%
“…However, by month four of storage, the amylose content did not differ between the RF-treated and untreated rice (Table 3). This result correlated with Patindol et al (2005) and Abeysundara et al (2017), who showed that high storage temperatures lowered amylose content in stored rice. The storage temperatures began to climb in the fourth month of our study, coincident with the arrival of the hot season.…”
Section: Discussionsupporting
confidence: 81%
“…High temperatures cause faster degradation reactions so that materials stored at high temperatures will experience a faster reduction in amylose content. The same results were also observed by Abeysundara et al (2017) with 13 weeks of storage in the Bathalegoda and Ambalangoda rice varieties (Sri Lanka rice varieties) a decrease in amylose levels. The decrease in amylose content was 0.72% for the bathalegoda variety.…”
Section: Chemical Parametersupporting
confidence: 80%
“…The amylose content of rice in all samples decreased (Figure 6), this was because amylose was used as energy for metabolism during storage (Abeysundara et al, 2017). The amylose enzyme remained active during rice storage although its activity decreased over time.…”
Section: Chemical Parametermentioning
confidence: 96%
See 1 more Smart Citation